The Plasmodium circumsporozoite protein - Singer, Mirko; Kanatani, Sachie; Castillo, Stefano Garcia; Frischknecht, Friedrich; Sinnis, Photini (Trends in parasitology, 2024)
The circumsporozoite protein (CSP) is one of the most studied proteins of the malaria parasite. It is the target of the only licensed malaria vaccines and is essential for sporozoite formation and infectivity. Yet, the mechanisms by which CSP functions and its interactions with other proteins are only beginning to be understood. Here we review the current state of knowledge of CSP structure and function, as sporozoites develop in the mosquito and establish infection in the mammalian host, and outline outstanding questions that need to be addressed.